SOSIALISASI BUDAYA GEMAR MEMBACA ANAK-ANAK DI LINGKUNGAN KELUARGA PADA RT/RW. 003/000 KELURAHAN PERUMNAS WAY HALIM BANDAR LAMPUNG - Heny Herawati; Rasty Yulia (Pusat Riset dan Inovasi Nasional, 2022)
The objectives of implementing this cultural socialization of reading fondness are: (1) to find out what factors cause children’s interest in reading to be very low when compared to other countries in the world, (2) to find out the ways that parents do in cultivating the habit of reading books to their children, (3) encourage and improve literacy skills to create a society that is knowledgeable and characterized, (4) growing interest in reading in a family environment that cultivates reading as a necessity. Devotion method on the socialization of the culture of reading children in the family environment, at rt/rw: 003/000 kelurahan perumnas way halim bandar lampung, uses a PRA (participatory rural appraisal). The results of this discussion, there are 7 ways to make children love reading, namely: (1) important slogans about reading, (2) giving awards, (3) giving birthday gifts, (4) taking children to the library or reading park, (5) examples and examples, (6) reward, (7) give birthday gifts With the implementation of the cultural socialization of reading fondness, be able to encourage and improve literacy skills, to create a society of knowledge and character. It can also foster an interest in reading in children.